2016
DOI: 10.2106/jbjs.15.01004
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pain Management Among Dominican and American Health-Care Providers

Abstract: Our findings suggest that cross-cultural comparisons provide insight into how opioid prescribing practices, approaches to the patient-provider relationship, and medication access inform distinct pain management strategies in American and Dominican surgical settings. Integrating lessons from cross-cultural pain management studies may yield more effective pain management strategies for surgical procedures performed in the United States and abroad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…In order to better understand the analgesic prescription culture at HGPS and compare that to the practices of Op-Walk staff, Devine et al interviewed American and Dominican providers about their prescription patterns and decision-making frameworks 27 . Dominican surgeons rarely prescribed opioids because of limited availability, and adhered to a standardized pain protocol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to better understand the analgesic prescription culture at HGPS and compare that to the practices of Op-Walk staff, Devine et al interviewed American and Dominican providers about their prescription patterns and decision-making frameworks 27 . Dominican surgeons rarely prescribed opioids because of limited availability, and adhered to a standardized pain protocol.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Op-Walk Boston’s use of qualitative studies allowed for an increased understanding of the differences in medical practices, catalyzed adaptation to cultural norms, and identified needed interventions. For example, studies on patient opioid use and physician opinions on prescription medications showed that HGPS physicians rarely prescribed opioids, and patients had limited experience with them 27,28 . These observations prompted the Op-Walk clinical leaders to reduce the role of opioids in the postoperative pain management protocols for the program, as well as to evaluate the reasoning for their prescription practices at their home institutions.…”
Section: Discussionmentioning
confidence: 99%
“…27 In other countries, opioids are rarely used after surgeries that routinely merit an opioid prescription when performed in the United States. 5,13 Geographic variation in approaches to postoperative pain relief highlights the need for the standardization of prescribing practices and nationwide prescriber education on the topic. National, comprehensive educational programs coupled with procedure-specific quantitative guidelines would help to mitigate the cultural and geographic variation in prescriber behaviors.…”
Section: Figmentioning
confidence: 99%
“…10,21 This conflict has contributed to overprescribing, often leaving patients with leftover narcotic pills after surgery. 12,19,28 The push to reduce opioid prescriptions is further supported by the lack of an association between increased opioid dosage and pain relief, 5,13,25 multiple side effects (including death), 4 an association with postoperative complications, 4,8 and the legal ramifications of careless prescribing. 7 The American Academy of Orthopaedic Surgeons has called for the standardization of opioid prescribing practices in an attempt to decrease overprescribing and the number of pills available for diversion.…”
mentioning
confidence: 99%
“…variation in analgesic prescribing among countries for similar injuries remains poorly understood 7 . Although there have been several international studies of opioid prescribing practices in the Dominican Republic, the Netherlands, and China, these studies have been qualitative or retrospective, or have not addressed opioid prescribing after operative management [7][8][9] . We are aware of only a single quantitative comparative study of international postoperative opioid prescribing, which compared the U.S. and the Netherlands 10 .…”
mentioning
confidence: 99%